AB0156 Polysaccharides from dendrobium officinale ameliorate the development of murine sjögren's syndrome via inducing il-10-producing b cells. (12th June 2018) - Xiao, F.; Lin, X.; Liu, D.; Lu, L.
Abstract : Background: Primary Sjögren's syndrome (SS) is a chronic autoimmune disease with salivary gland (SG) hypofunction and inflammation. Currently, effective therapies for SS patients are still lacking. Polysaccharides derived from Dendrobium officinale (DOP) have been shown to possess immunomodulatory functions in various animal models. However, it remains unclear whether DOP can modulate immune responses and have potential therapeutic effects on SS. Objectives: To investigate the immune modulatory and therapeutic effects of DOP on experimental SS (ESS) in mice. Methods: Polysaccharides were extracted from Dendrobium officinale with removal of endotoxin. C57BL/6 mice were immunized with SG-derived proteins for ESS induction, followed by daily oral treatment of vehicle and different dosages of DOP. SG functions were assessed by monitoring saliva flow rates whereas lymphocytic infiltration and tissue destruction in SG were examined by histological analysis. Both T and B cell populations in peripheral lymphoid organs were analyzed by flow cytometry. The effects of DOP on IL-10-producing B cell (B10 cell) induction and Th17 cell differentiation were examined in culture. Moreover, TLR4 and TLR9 inhibitors were used to identify the function of TLR4/TLR9 in DOP-mediated effects. Results: ESS mice with DOP treatment displayed significantly higher saliva flow rates than vehicle-treated ESS mice. DOP treatment ameliorated SG tissue destruction accompanied with profoundly reduced lymphocytic infiltration in ESS mice when compared with vehicle-treated counterparts. Moreover, DOP treatment markedly increased the numbers of B10 cells but decreased numbers of Th17 cells in peripheral lymphoid organs of ESS mice. Notably, DOP markedly increased frequencies and numbers of B10 cells but did not affect Th17 cells generation in culture. Moreover, TLR4 inhibitor, but not TLR9 inhibitor, significantly suppressed DOP-induced IL-10 production in B cells Conclusions: The results show that DOP treatment ameliorates ESS disease development by inducing regulatory B10 cells, suggesting that DOP might be a promising candidate for treating SS. References: [1] Ng TB, et al. Review of research on Dendrobium, a prized folk medicine. Appl. Microbiol. Biotechnol 2012;93:1795–1803. [2] Xiao F, et al. Proteasome inhibition suppresses Th17 cell generation and ameliorates autoimmune development in experimental Sjögren's syndrome. Cell. Mol. Immunol 2017. Disclosure of Interest: None declared